2017
DOI: 10.1002/mgg3.329
|View full text |Cite
|
Sign up to set email alerts
|

Panel‐based whole exome sequencing identifies novel mutations in microphthalmia and anophthalmia patients showing complex Mendelian inheritance patterns

Abstract: BackgroundMicrophthalmia and anophthalmia (MA) are congenital eye abnormalities that show an extremely high clinical and genetic complexity. In this study, we evaluated the implementation of whole exome sequencing (WES) for the genetic analysis of MA patients. This approach was used to investigate three unrelated families in which previous single‐gene analyses failed to identify the molecular cause.MethodsA total of 47 genes previously associated with nonsyndromic MA were included in our panel. WES was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Recent studies reported that the rate of mosaicism could be as high as 17.5% among apparent de novo cases for different dominant disorders [83,107]. Indeed, several reports have suggested mosaicism as the cause for the variable phenotypes seen in some sporadic PAX6-affected patients [83,93,108,109]. A recent study from Tarilonte et al proved the existence of post-zygotic parental mosaicism in three unrelated Spanish families with variable aniridia or microphthalmia phenotypes caused by heterozygous nonsense (c.771G>A, p.Trp257* and c.120C>A, p.Cys40*) or missense (c.178T>C, p.Tyr60His) PAX6 mutations, respectively [110].…”
Section: Inheritance Of Pax6 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported that the rate of mosaicism could be as high as 17.5% among apparent de novo cases for different dominant disorders [83,107]. Indeed, several reports have suggested mosaicism as the cause for the variable phenotypes seen in some sporadic PAX6-affected patients [83,93,108,109]. A recent study from Tarilonte et al proved the existence of post-zygotic parental mosaicism in three unrelated Spanish families with variable aniridia or microphthalmia phenotypes caused by heterozygous nonsense (c.771G>A, p.Trp257* and c.120C>A, p.Cys40*) or missense (c.178T>C, p.Tyr60His) PAX6 mutations, respectively [110].…”
Section: Inheritance Of Pax6 Mutationsmentioning
confidence: 99%
“…MAC is a group of developmental eye disorders characterised by reduced size orabsence of the ocular globe and it is caused by mutations in more than 90 genes, including PAX6 (Figure 4) [92]. Of the 13 different mutations that are associated with microphthalmia in the PAX6 Mutation Database, the vast majority (8) are missense, although PTC-inducing mutations have been reported (two nonsense and two frameshifts) ( Figure 5) [108,110,135,136]. Bilateral microphthalmia in a patient with WAGR syndrome was also identified [137].…”
Section: Microphthalmia Anophthalmia and Coloboma (Mac)mentioning
confidence: 99%
“…[Tyr132Asn], NM_006744) in a proband with an isolated bilateral complex microphthalmia phenotype (Riera et al 2017). Moreover, a WES study has identified a homozygous mutation predicted to affect RBP4 splicing (c.248+1G>A, NM_006744) in a patient with unilateral microphthalmia, retinal dystrophy and bilateral iris and retinal coloboma (Khan et al 2017).…”
Section: Rbp4 (Retinol Binding Protein 4)mentioning
confidence: 99%
“…Advances in next-generation sequencing technology will allow for the identification of previously unknown deletions, duplications, inversions and translocations, as well as non-coding and splice variants [11]. Whole exome sequencing/whole genome sequencing (WES/WGS) screens all coding genes/the whole genome, which can increase the identification of novel disease-associated variants, including genes in associated loci where no candidate gene has yet been identified (Table 1), as well as eliminate loci which have been incorrectly associated with a disease [9,12]. The major genes associated with anophthalmia broadly fall into two distinct categories (i) eye field initiating transcription factors, such as SOX2 (OMIM: 184429) and OTX2 (OMIM: 600037), or (ii) retinoic acid signalling pathway components, including STRA6 (OMIM: 610745), ALDH1A3 (OMIM: 600463) and RARB (OMIM: 180220) [10,13,14].…”
Section: Mutational Spectrummentioning
confidence: 99%